Relocation and Inequalities between Skilled and Unskilled in Northern Countries: Simulation Using a CGE Model - Raouf, Radouane; Hafid, Hicham (International Journal of Economics and Financial Issues, 2014)
The aim of this paper is to analyze the impact of offshoring on employment in France. In economic analysis, is often associated the phenomenon of relocation to the problem of unemployment. Using a Computable General Equilibrium Model (CGEM), we simulate the relationship between offshoring to the CEECs and the rising inequality between skilled (TQ) and unskilled (TNQ) workers. In order to study this impact, we will initially talk about theoretical and empirical contributions explaining the relation “relocation-employment”. In a second step, we will develop a CGE model (the model is implemented in GAMS) to test the impact of offshoring to the CEECs on wage and unemployment rate for skilled and unskilled workers. The simulation results show that there is a negative effect of offshoring on the situation of TNQ in terms of wages and employment and a rather positive effect on TQ. This confirms the “Stolper-Samuelson” theorem. Keywords: Relocation; FDI; Skilled and Unskilled workers; Inequality; Wage; CGEM. JEL Classifications : F12 ; F16 ; F21